Liquidity management around seasoned equity offerings - Slu, David T.L.; Faff, Robert W. (Penerbit Universiti Kebangsaan Malaysia, 2014)
We investigate firms' liquidity practices around seasoned equity offerings (SEOs). We broadly classify issuers on the basis of whether the firm belongs to an industry deemed to be financially constrained or unconstrained. We find that constrained-industry issuers tend to save more cash to conserve funding capacity in anticipating investment. Unconstrained industry issuers, in contrast, carry high debt and limited cash reflecting a sizable financial leash. We also find that the former firms experience significant cash stockpiling following new equity issues, whereasforthe lattergroup, there is a significant decline in long-term debt. In the long run, unconstrained issuers who aggressively manage liquidity pre-issue have lower operating profit. However, the relation does not hold for market-based performance because investors, observingthe liquidity information, quickly discount stock value at the time of the offering. Rather, post-issue market underperformance can be attributed to investors' downward revisions relating to the transitory nature of investment opportunities.